PhylloTrees: Harnessing Nature's Phyllotactic Patterns for Tree Layout - Carpendale, Sheelagh; Agarawala, Anand (InfoVis'04: Poster Compendium of the IEEE Symposium on Information Visualization, 2004)
We explore the use of nature’s phyllotactic patterns to inform the layout of hierarchical data. These naturally occurring patterns provide a non-overlapping, optimal packing when the total number of nodes is not known a priori. We present a family of expandable tree layouts based on these patterns.